Performance of high-level Spanish athletes in the Olympic Games according to gender - Leiva-Arcas, Alejandro; Vaquero-Cristóbal, Raquel; Abenza-Cano, Lucía; Sánchez-Pato, Antonio (PLOS ONE, 2021)
No studies have been found that analyzed the probabilities of high-level athletes according to gender for accessing programs that promote the professionalization of sports, and participation and success in the OG in Spain. This could explain the gender differences in these parameters and the trend towards more egalitarian data in recent years. The objective of this study was to analyze the probabilities of Spanish high-level athletes for participating and achieving sporting success in the 2008, 2012 and 2016 Olympic Games (OG). Data relating to a sample of 3757 high-level Spanish athletes (2398 men and 1359 women) between 2005 and 2016 were examined. The variables of gender, having obtained a scholarship from the Association of Olympic Athletes (ADO) program, training in a High Performance Center (CAR), participation and performance in the OG were analyzed. It was found that high-level female athletes were more likely than male athletes to belong to the ADO program (χ2 = 26,151; r* = 0.083; p = 0,000) and CAR (χ2 = 13,847; r* = 0.061; p = 0,000), and to qualify for an OG (χ2 = 22,838; r* = 0,078; p = 0,000), the same trend was found in the three Olympic cycles analyzed. With respect to the results in the OG, in general, no differences were found according to gender, although women were more likely to be finalists (χ2 = 4,406; r* = 0.071; p = 0,036), and more prominently in the 2016 OG (16.118; r* = 0.228; p = 0.000). The same applies to winning a medal (χ2 = 5.939; r* = 0.145; p = 0.015), more specifically bronze at the 2012 OG (χ2 = 6.215; r* = 0.149; p = 0.013). In conclusion, high-level female athletes in Spain have a higher percentage of access to high-level athlete support programs such as ADO and CAR, as well as participation in OG.